2014
DOI: 10.1002/jcaf.22016
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Issues Related to Bitcoins

Abstract: Despite the frequent mention of Bitcoin in recent years in the press and business publications, many people are still uncertain what this cryptocurrency is or how it works. And although bitcoins (BTCs) are now an accepted medium of exchange for some businesses and not‐for‐profit organizations, no specific accounting guidance has been issued for these transactions. This article provides some basic information about BTCs and addresses six specific financial accounting issues: asset classification, mining activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 2 publications
1
26
0
8
Order By: Relevance
“…The Estonian e-residency initiative [36] raises concerns regarding identity authentication and the possible consequences of displacing responsibilities. This is in line with the call for individual accountability [5,6]. Our initial empirical work showed that the interactions between existing authorities and blockchain records are far from settled.…”
Section: A Proposal For Tribal Governancesupporting
confidence: 80%
See 1 more Smart Citation
“…The Estonian e-residency initiative [36] raises concerns regarding identity authentication and the possible consequences of displacing responsibilities. This is in line with the call for individual accountability [5,6]. Our initial empirical work showed that the interactions between existing authorities and blockchain records are far from settled.…”
Section: A Proposal For Tribal Governancesupporting
confidence: 80%
“…Copies are not all the same as they used to be. This is fostered by the open nature of the Bitcoin blockchain where no single node can be held accountable due to its distributed nature [5,6]. Traditional jurisdictions thereby may act as a mediating entity in case of disputes only to the extent concerned parties accept it.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…18 for such a treatment. In accordance with practice-oriented articles (Raiborn and Sivitanides, 2015;Tan and Low, 2017), the paper argues that faithful representation varies with reporting entities and depends on their actual business model along with the economic reality of the underlying transaction. Mining of cryptocurrencies shall, therefore, follow different accounting principles other than receiving payments in cryptocurrencies or investing into cryptocurrencies.…”
Section: Introductionmentioning
confidence: 68%
“…From the accounting perspective, cryptocurrencies are investment assets, sometimes even treated similarly to stocks for accounting purposes(Raiborn and Sivitanides 2015).…”
mentioning
confidence: 99%